Breastfeeding Knowledge, Attitude, And Practices and Its Association with Food Insecurity During COVID-19 - Abdul Hamid , Syahrul Bariah; Haris, Syasya Nurazmiena; Hui , Jun Chih (Environment-Behaviour Proceedings Journal, 2022)
Introduction: Child hunger commonly occurs in families with household food insecurity when mothers fail to continue breastfeeding due to stress and inability to produce sufficient breastmilk. This study aimed to investigate the association of breastfeeding KAP with food insecurity during the pandemic of COVID-19. Method: An online self-administered questionnaire related to the study was used to obtain data from 444 Malaysian Result: Findings showed that majority of the mothers have moderate to good KAP of breastfeeding. However, food insecurity and child hunger still occur. Conclusion: These findings may be helpful for healthcare professionals in developing effective strategies for efficient breastfeeding during the pandemic.